The dream and the unconscious in the psychologic analyses - شباني, منذر; خضور , رهف (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This search have taken the talking about dreaming in order to identify its essence which related with the psychological vitality . Dreaming comes from an awareness organized and capable to farming the relations between the ideas which look like uncorrelated thinking dreaming has the ability to combining between the deep nature of someone which appears in the dreaming site and the consciousness site which select the dream elements from the reality , reshape it to a dream substance . Also this search shows that relations between the unconscious and the dream through interpretation "dreaming issue " which lead us to what Freud call it " twisting the dream " and this " twisting the dream " could be the conflict between the ID and the ego ideal and between what is conscious and unconscious . At the end the search clarify how the psychologic analyses could refer to the problems which related to the explanations which have the previous rules in dream explain to find that all this problems variety according to the nature of dream and according to the linchpins of its explanations or twisting it